The two behavioural risk factor surveillances on the adult and elderly populations as information systems for leveraging data on health-related sustainable development goals in Italy. (August 2021) - Possenti, Valentina; Minardi, Valentina; Contoli, Benedetta; Gallo, Rosaria; Lana, Susanna; Bertozzi, Nicoletta; Campostrini, Stefano; Carrozzi, Giuliano; Cristofori, Marco; D'Argenzio, Angelo; De Luca, Amalia; Fateh-Moghadam, Pirous; et al.
Highlights: Noncommunicable diseases are major contemporary challenges to public health. Behavioural risk factor surveillances provide context data useful to health planning. Such systems inform several health-related Sustainable Development Goals. Surveillance relevance increases in Public Health Emergency of International Concern. Abstract: Introduction: Current lengthening of average life and constant increase of population ageing associated to forces that include rapid unplanned urbanisation and globalisation of unhealthy behaviours have determined the huge relevance of noncommunicable diseases (NCDs). Monitoring key modifiable behavioural risk factors has resulted to be crucial both in spatial terms and as per temporal trends in order to allow comparisons between different geographic areas or levels and over time. Materials and Methods: In Italy, PASSI (Progressi delle Aziende Sanitarie per la Salute in Italia) and Passi d'Argento are the ongoing Behavioural Risk Factor Surveillance Systems (BRFSSs), respectively, on adults (people aged 18−69) and elderly (65 and older). Results: The two Italian surveillances are information systems providing data not only on the third Sustainable Development Goal (SDG) that explicitly addresses ensuring healthy lives and promoting well-being for all, but on a total of nine health-related SDGs (HRSDGs) and 19 HRSDG targets/indicators. We describe these pairs more in detail specifying where in case of BRFSS core indicators (N = 14 HRSDG targets/indicators) concerning six HRSDGs or, on the other hand, as per BRFSS further in-depth analysis (N = five HRSDG targets/indicators) in regard of four different HRSDGs. About the HRSDG 3, HRSDG target 3.4, HRSDG indicator 3.4.1, from the PASSI and Passi d'Argento data it is possible not only to detect the prevalence of NCDs in adults and elderly living in Italy, but also to evaluate the social determinants of health, such as gender, age group, educational level, economic difficulties, as well as the associations with modifiable lifestyle risk factors. Conclusions: The two Italian BRFSSs generate accurate data, which are highly relevant to design, implement, monitor, and evaluate programs and policies at different levels (local, regional, national) for NCD prevention and health promotion. They provide numbers which can also serve as propaedeutic or, in some cases, complementary ground to address a robust measurement of several HRSDG patterns.